Beware of the ‘telephone effect’: the influence of telephone transmission on the measurement of formant frequencies - Kunzel, Hermann J. (International Journal of Speech, Language and the Law, 2001)
Speech scientists often have to work with speech signals that have been transmitted over the telephone. Although the acoustic properties of telephone transmission such as the band-pass filter characteristics are well known, little attention has been paid to their effect on the measurement of speech parameters. This study deals with artefacts introduced by the lower cut-off slope of the transmission channel on vowel formants. For theoretical reasons, frequency components may be assumed to be attenuated the lower they are. Therefore F1 of most vowels can be expected to be affected most. Attenuation of the lower components of a formant will necessarily increase the relative weight of the higher components for the determination of a formant and thus cause an artificial upward shift of its centre frequency. An empirical investigation with directly and telephone-transmitted samples from ten male and ten female subjects shows that the predicted effect on F1 does in fact occur for all tested vowels except /a/, whose F1 is too high to be affected by the slope of the band-pass. The consequences of measurement errors arising from such artefacts are discussed with special reference to speaker identification and empirical dialectology.